IMPLEMENTASI KECERDASAN EMOSIONAL (EQ) DAN KECERDASAN SPIRITUAL (SQ) PADA PEMBELAJARAN PAI DI SEKOLAH - Nudin, Nurhasan; Zulfitria, Zulfitria; Mutaqqinasiht, Latifah Rhamadona (Universitas Garut, 2024)
This research aims to examine the literature regarding the implementation of SQ and EQ in PAI learning in the school context. The approach used in this research is a literature review with a focus on studies of SQ and EQ implemented in PAI learning. The data sources used in this literature review are articles that have been published in various journals. The results of the literature review show that the implementation of EQ in PAI learning at school can be done with reflection activities, managing emotions, and applying positive values. Furthermore, the implementation of SQ in PAI learning can be carried out by applying religious values in daily life and creating religious activity programs that involve students directly